Relative Expression of PPARγ and ADIPOQ mRNA as markers of Inhibition Adipogenesis on Mesenchymal Stem Cells after Pulsed Electromagnetic Field (PEMF) Exposure - Puji Sari (Journal of Global Pharma Technology, 2020)
ABSTRACTObjective: Obesity has become a major health problem in the world. PEMF is a modality for healing obesity because its ability to inhibit adipogenesis. Adipogenesis involves PPARγ transcription factor which plays a role in activating adipogenic genes, including ADIPOQ. PPARγ is highly expressed in the early stages of adipogenesis and ADIPOQ is highly expressed in the termination phase of adipogenesis. Both of these genes can be used as a marker of adipogenesis. This study aimed to determine the level of PPARγ and ADIPOQ expression in the group of MSCs that were exposed to PEMF and the group of MSCs that were not exposed to PEMF.Methods: The MSCs were exposed with PEMF intensity of Bmax = 2 mT, f = 75 Hz, 10 minutes a day for 14 days. Total RNA was extracted from MSCs from each treatment group on day 0 (calibrator), 2, 4, 7, and 14. PPARγ and ADIPOQ mRNA expressions were analyzed using the qRT-PCR method.Results: The results of the qRT-PCR analysis showed that the expression of PPARγ and ADIPOQ mRNA in the group that exposed to PEMF was lower than the group of MSCs that were not exposed to PEMF (p <0.05).Conclusion: PEMF exposure has an inhibitory effect on adipogenesis of MSCs. PEMF exposure decreased the relative expression of PPARγ and ADIPOQ mRNA. Keywords: PEMF; Adipogenesis; Mesenchymal stem cells; PPARγ, ADIPOQ.